2015
DOI: 10.1080/09715010.2015.1016125
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nonlinear sorption on multispecies radionuclide transport in a coupled fracture-matrix system with variable fracture aperture: a numerical study

Abstract: A one-dimensional numerical analysis on multispecies radionuclide transport in a single-horizontal coupled fracture-matrix system has been performed. Analysis considering linear and nonlinear adsorption cases with linear, Langmuir, and Freundlich adsorption models has been carried out. The results indicate that there is a significant change in the spatial distribution of radionuclides in a coupled fracture-matrix system when a nonlinear adsorption isotherm is considered as compared to the simplified linear sor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Details of the problems for the first and second cases, including retardation coefficient (R m ), decay coefficient (šœ† ), initial and boundary conditions, etc., are described in Table (1). It is worthwhile to mention that in tables and figures below, the first and second case studies are referred to as the analytical results of dimensionless concentration for the three The results of numerical experiments for the first and second test cases are summarized in figures ( 1) and ( 2) and Tables (2-4).…”
Section: Numerical Investigationmentioning
confidence: 99%
“…Details of the problems for the first and second cases, including retardation coefficient (R m ), decay coefficient (šœ† ), initial and boundary conditions, etc., are described in Table (1). It is worthwhile to mention that in tables and figures below, the first and second case studies are referred to as the analytical results of dimensionless concentration for the three The results of numerical experiments for the first and second test cases are summarized in figures ( 1) and ( 2) and Tables (2-4).…”
Section: Numerical Investigationmentioning
confidence: 99%
“…For example, Zhang et al [11] suggested a 1D model based on FEM for multi-component solute transport in saturated soil. Bagalkot and Suresh Kumar [12] presented a 1D numerical evaluation of the FDM for multi-species radionuclide transport in a single horizontally coupled fracture-matrix system. Mostaghimi et al [13] and Maheshwari et al [14] investigated the effect of pore structure heterogeneity on reactive transport using a 3D pore scale model based on FVM.…”
Section: Introductionmentioning
confidence: 99%
“…Torlapati (2013) proposed a multi-component reactive transport model by using explicit forms of backward difference FDM, total variation diminishing schemes, and fully implicit approaches to predict the fate and transport of biochemical and geochemical reactive transport problems in a 1D condition. Bagalkot and Kumar (2015) introduced a 1D numerical assessment with FDM for multispecies radionuclide transport in a single-horizontal coupled fracture-matrix system. Sharma et al (2016) investigated the impact of distance-dependent dispersion on multispecies solute transport process with upwind-and central-difference approaches of implicit FDM, as well as constant, linear, and exponential dispersivity functions.…”
Section: Introductionmentioning
confidence: 99%